2007
DOI: 10.1109/tpami.2007.40
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Biologically-Inspired Scene Classification Using Features Shared with Visual Attention

Abstract: We describe and validate a simple context-based scene recognition algorithm for mobile robotics applications. The system can differentiate outdoor scenes from various sites on a college campus using a multiscale set of early-visual features, which capture the "gist" of the scene into a low-dimensional signature vector. Distinct from previous approaches, the algorithm presents the advantage of being biologically plausible and of having low-computational complexity, sharing its low-level features with a model fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
330
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 502 publications
(333 citation statements)
references
References 40 publications
1
330
0
2
Order By: Relevance
“…Recently, saliency detection has been widely used in many computer vision applications, and in particular, several works [39,50,51] have reported that saliency-based sampling can help to improve the performance in scene classification. Visual saliency is the perceptual ability of a vision system (e.g., human) to focus on the interesting information while ignoring irrelevant information.…”
Section: Feature Coding Based On the Saliency Mapmentioning
confidence: 99%
“…Recently, saliency detection has been widely used in many computer vision applications, and in particular, several works [39,50,51] have reported that saliency-based sampling can help to improve the performance in scene classification. Visual saliency is the perceptual ability of a vision system (e.g., human) to focus on the interesting information while ignoring irrelevant information.…”
Section: Feature Coding Based On the Saliency Mapmentioning
confidence: 99%
“…Borji et al learned a Bayesian network that has some feature variables (scene gists [108], bottom-up saliency maps, game controllers, game events) connected to the corresponding eye positions and incorporated MEP (mean of the distribution of all training eye positions) as a prior distribution [109]. The approach obtained higher prediction of eye fixations than classical discriminative classifiers, including regression, support vector machine, and k nearest neighbor.…”
Section: Weighted Combination Of Bottom-up and Top-downmentioning
confidence: 99%
“…1) The video is partitioned into video frames, which are represented by GIST and saliency maps [11].…”
Section: A Multimedia Data Representationmentioning
confidence: 99%